Unusual case of simple urinary bladder melanosis with complete resolution. (25th April 2018) - Mera, Zaid; Patel, Sheena; Qassid, Omar; England, Roland
Abstract : A 66-year-old man presented with a long history of recurrent attacks of urinary retention and lower urinary tract symptoms. Flexible cystoscopy showed a urethral stricture. Follow-up cystoscopy 7 years later for recurrent symptoms demonstrated unusual extensive mucosal brown to black pigmentation, which proved histopathologically to be a simple bladder melanosis. Follow-up demonstrated complete resolution over a period of 1 year with no specific treatment. In this report, we highlighted a rare bladder abnormality with uncertain natural history.